The Impact of Macroeconomic Policies on Healthcare Delivery in Kenya: An Analysis of the National Sexual Violence Prevention and Care Response. (October 2021) - Munala, Leso; Welle, Emily; Okunna, Nene; Hohenshell, Emily
Sexual violence is one of the most common forms of violence against women in Kenya. This study documents the care of sexual violence survivors from the perspective of health care practitioners based on an analytic framework developed in studies of the political-economy of health to examine the effects of International Financial Institutions' conditionalities on the allocation of national fiscal resources. The study documented the working conditions of practitioners and myriad challenges that they experience in providing quality services to sexual violence survivors. The issues reflected in the results are grounded in social structural inequities driven by the global political economic policies that perpetuate poverty and dependency throughout Africa and the developing world. Macro-level variables associated with health care provision are assessed with a focus on global macroeconomic policies established by the International Monetary Fund and World Bank, their impact on Kenya's health economy and their ultimate impact on the capacity of the health system to meet the complex needs of survivors of sexual violence. In this paper, study results are analysed within the context of these macroeconomic policies and their legacy.